ANALISIS ANGKUTAN SEDIMEN DASAR (BED LOAD) PADA SUNGAI SELOR DI KECAMATAN TANJUNG SELOR KABUPATEN BULUNGAN - Singal, Rachel Zandra; Nur, Mardhawiah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
ABSTRACT: Selor River is 6.7 km long, which passes through Buluh Perindu and Tanjung Rumbia areas in Kelurahan Tanjung Selor Hilir. The condition of Selor River is mostly sediment accumulation in several parts of the Selor River flow. The sedimentation problem that occurs continuously will cause shallowing which will affect the reduction in the flow capacity of the Selor River. The purpose of this study was to determine the bed load in the Selor River flow. Sediment data collection in the Selor River flow at four points using the purposive random sampling method. Sediment sampling at these four points was to fulfill the factors for sedimentation formation and to represent sediment conditions along the Selor River flow. Analysis of the large bed sediment load using the Mayer Petter Muller method using measurement data on one wet cross-section, average water depth, average speed, river bed slope and bed sediment grain diameter for bed sediment calculations. The sampling of bottom sediment was continued with sample testing at the Bina Marga DPUPR Kabupaten Bulungan laboratory, obtained data on sediment water content, sediment specific gravity and sieve analysis, resulting in a large bottom sediment grain diameter of D90 and from the sieve analysis it was produced that the diameter of grains passing sieve No. 4 (4,750 mm) was 98.4%; passing sieve No. 90 (0.175) was 23.33%. The results of the analysis of the large load of bottom sediment transport in the Selor River in the form of a bottom sediment discharge in a period of one day of 5.9616 Tons/day, a bottom sediment discharge in a period of one year of 2,175.984 Tons/year. Keywords: Bed Load Sediment, Sedimentation, Debit Sediment, Selor River, Mayer Petter Muller. ABSTRAK: Sungai Selor memiliki panjang 6,7 Km, yang melewati daerah Buluh Perindu dan Tanjung Rumbia wilayah Kelurahan Tanjung Selor Hilir. Kondisi Sungai Selor sebagian besar terjadi penumpukan sedimen pada beberapa bagian aliran Sungai Selor. Permasalahan sedimentasi yang terjadi tersebut secara terus menerus akan menyebabkan pendangkalan yang berpengaruh terhadap penurunan kapasitas aliran sungai Selor. Tujuan dari penelitian ini adalah untuk mengetahui debit sedimen dasar (bed load) pada aliran Sungai Selor. Pengambilan data sedimen di aliran Sungai Selor pada empat titik dengan metode pengambilan data adalah menggunakan metode purposive random sampling. Pengambilan sampel sedimen pada empat titik ini adalah untuk memenuhi faktor- faktor terbentuknya sedimentasi dan dapat mewakili kondisi sedimen sepanjang aliran Sungai Selor. Analisis besar muatan sedimen dasar dengan mengunakan metode Mayer Petter Muller dengan menggunakan data ukur pada satu penampang basah, kedalaman air rata-rata, kecepatan rata-rata, kemiringan dasar sungai dan diameter butiran sedimen dasar (bed load) untuk perhitungan sedimen dasar (bed load). Pengambilan sampel sedimen dasar dilanjutkan dengan pengujian sampel di laboratorium Bina Marga DPUPR Kabupaten Bulungan diperoleh data kadar air sedimen, berat jenis sedimen dan analisa saringan, dihasilkan besar sedimen dasar diameter butiran D90 dan dari analisa saringan dihasilkan diameter butiran lolos saringan No.4 (4,750 mm) adalah 98,4% ; lolos saringan No.90 (0,175) adalah 23,33%. Hasil analisis besar muatan angkutan sedimen dasar pada sungai Selor berupa debit sedimen dasar dalam jangka waktu satu hari sebesar 5,9616 Ton/hari, debit sedimen dasar dalam jangka waktu satu tahun sebesar 2.175,984 Ton/tahun.Kata kunci: Sedimen Dasar, Sedimentasi, Debit Sedimen, Sungai Selor, Mayer Petter Muller.